2018
DOI: 10.1155/2018/1648652
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical Efficacy of Salbutamol with Jet and Mesh Nebulizers in Asthmatic Children

Abstract: Background Ultrasonic, jet, and mesh nebulizers have all been used in the treatment for asthma. Mesh nebulizers reportedly offer the best inhalation efficiency. Methods This study aimed to clarify the utility of the mesh nebulizer, compared to jet nebulizers, in the treatment of pediatric asthma patients. Participants included 88 children <6 years old who were receiving treatment for asthma at Murayama Pediatric Clinic. Heart rate, peripheral oxygen saturation in arterial blood, and Mitsui symptom scores were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…For the children younger than 2 years, the heart rate increment was not significant. They concluded that the dose of salbutamol solution might be excessive for the older age group [10]. In our study, adverse effects were similar in both nebulizers, but the complaint of palpitation was significantly higher in the MN group.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…For the children younger than 2 years, the heart rate increment was not significant. They concluded that the dose of salbutamol solution might be excessive for the older age group [10]. In our study, adverse effects were similar in both nebulizers, but the complaint of palpitation was significantly higher in the MN group.…”
Section: Discussionsupporting
confidence: 49%
“…Although some differences in lung function improvement had been detected, all 3 mesh nebulizers were found to be useful devices in treating bronchial asthma [9]. A clinical [10]. We did not compare the inhalation time, but we observed similar degrees of improvement in lung functions after beta 2 - agonist inhalation in both groups.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, comparative studies on salbutamol delivery efficiency in various types of nebulizers have mostly been based on the use of a breathing simulator with mechanical ventilation, a humidifier, and breathing masks [14,16]. A few clinical studies have compared the efficacy, admission rates, and total dose of salbutamol used by jet and mesh nebulizers in asthmatic children and emergency rooms [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, nebulization products for chronic and rare diseases are available on the market for coupling with a dedicated tested nebulizer [15,16,17,18]. In fact, variability in dose delivery from different nebulizers has been reported [8,19,20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%